Digital due diligence : a complementary perspective to the traditional approach - Turuk, Mladen (Array, 2020)
Mergers and acquisitions (M&A) represent one of the most common ways for firms to achieve non-organic growth, and one of the main stages in the typical M&A transaction is due diligence of the target company. The aim of this paper is to provide a guideline for conducting due diligence process in the digital environment. After a brief introduction on the nature, purpose and elements of the due diligence, the paper elaborates various risks, and psychological and contextual hazards often occurred during due diligence process. Special attention has been paid to the elaboration of the role and importance of the digital due diligence as a new concept in today’s contemporary ‘digital’ economy. The outcome of this paper is to provide a comparison between ‘traditional’ and ‘digital’ due diligence, digital due diligence methodology, and easy understandable check list for conducting the process of digital due diligence.